Characterization and application of overriding mandatory provisions: reflections on judgment E.N.I. and Y.K.I. v. HUK-COBURG-Allgemeine Versicherung AG - Ferrario, Tommaso (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In the judgment 5th September 2024, E.N.I. and Y.K.I. v. HUK-COBURG-AllgemeineVersicherung AG, the Court of Justice ruled on the characterization and application of a provision ofBulgarian law as overriding mandatory rule under article 16 of Rome II regulation. The decision addressedissues of both theoretical and practical significance, outlining the interpretative and applicativecontours of mandatory provisions and giving an important contribution to the definition of this conceptin European private international law.
Keywords: Overriding mandatory rules; Ordre public; Ascertainment of foreign law; European private international law